PENGARUH KOMPENSASI TERHADAP KOMITMEN ORGANISASI KARYAWAN: (STUDI PADA BADAN PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA PROVINSI JAWA BARAT) - Frengki Ferdian A; Astadi Pangarso (VALUTA, 2016)
The purpose of this study is to determine how much is the influence of the compensation to organizationalcommitment. The x variable was compensation, while the y variable is the organization's commitment.This research used quantitative methods with causality descriptive research type. The population in thisstudy were the employees of Woman Empowerment, Child Protection And Family Planning Board OfWest Java Province, using saturated sampling techniques. Based on research result, there is a positiveand significant impact of employee compensation to organizational commitment. The result ofcompensation determination influenced 9.3% to the employee’s organizational commitment of WomanEmpowerment, Child Protection And Family Planning Board Of West Java Province and the rest 90,7 %influenced by another factors outside this research.